Le projet pédagogico-didactique de socialisation : perspective d'une socialisation démocratique pour l'enseignement-apprentissage des questions environnementales et de développement - Melki Slimani; Jean-Marc Lange; Atf Azzouna (Presses universitaires de la Méditerranée, 2018)
This contribution is a reflection on the educational purposes as conditions of possibility of a pedagogical-didactic synergy in the analysis and the elaboration of educational situations. This reflection focuses, then, on the possibility of socialization purposes in the management of situations in science education, scientific uncertainty education, eco-citizenship education and sustainable development education. This makes it possible to aim for the construction of a conceptual framework articulating learning moments linked to socialization in educational situations involving environmental and development issues.